Recent advances in information systems and technologies. Volume 2 - Rocha, Álvaro; Correia, Ana Maria; Adeli, Hojjat, 1950-; Reis, Luís Paulo, 1970-; Costanzo, Sandra (Springer, 2017)
This book presents a selection of papers from the 2017 World Conference on Information Systems and Technologies (WorldCIST'17), held between the 11st and 13th of April 2017 at Porto Santo Island, Madeira, Portugal. WorldCIST is a global forum for researchers and practitioners to present and discuss recent results and innovations, current trends, professional experiences and challenges involved in modern Information Systems and Technologies research, together with technological developments and applications. The main topics covered are: Information and Knowledge Management; Organizational Models and Information Systems; Software and Systems Modeling; Software Systems, Architectures, Applications and Tools; Multimedia Systems and Applications; Computer Networks, Mobility and Pervasive Systems; Intelligent and Decision Support Systems; Big Data Analytics and Applications; Human--Computer Interaction; Ethics, Computers & Security; Health Informatics; Information Technologies in Education; and Information Technologies in Radiocommunications.
Includes author index.
Keywords: Information technology -- Congresses.; Computer science -- Congresses.; Computer networks -- Congresses.; elektronické knihy; electronic books